Answer:
16 b plus a is mathematically plus 185 so 15
Answer:
<h2>
![(h - g)( - 2) = 18](https://tex.z-dn.net/?f=%28h%20-%20g%29%28%20-%202%29%20%3D%2018)
</h2>
Step-by-step explanation:
g(x) = x² - 2x - 6
h(x) = 2x² - 5x + 2
To find (h-g) (-2) we must first find h - g(x)
To find h - g(x) subtract g(x) from h(x)
We have
<h3>
![(h - g)(x) = {2x}^{2} - 5x + 2 - ( {x}^{2} - 2x - 6) \\ = {2x}^{2} - 5x + 2 - {x}^{2} + 2x + 6 \\ = {2x}^{2} - {x}^{2} - 5x + 2x + 2 + 6](https://tex.z-dn.net/?f=%28h%20-%20g%29%28x%29%20%3D%20%20%7B2x%7D%5E%7B2%7D%20%20-%205x%20%2B%202%20-%20%28%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20-%206%29%20%20%5C%5C%20%20%3D%20%20%7B2x%7D%5E%7B2%7D%20%20-%205x%20%2B%202%20-%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%202x%20%2B%206%20%5C%5C%20%20%3D%20%20%7B2x%7D%5E%7B2%7D%20%20-%20%20%7Bx%7D%5E%7B2%7D%20%20-%205x%20%2B%202x%20%2B%202%20%2B%206)
</h3><h3>
![(h - g)(x) = {x}^{2} - 3x + 8](https://tex.z-dn.net/?f=%28h%20-%20g%29%28x%29%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20-%203x%20%2B%208)
</h3>
To find (h-g) (-2) substitute the value of x that's - 2 into (h - g)(x) that's replace every x in (h - g)(x) by - 2
That's
<h3>
![(h - g)( - 2) = ({ - 2})^{2} - 3( - 2) + 8 \\ = 4 + 6 + 8 \\ = 10 + 8](https://tex.z-dn.net/?f=%28h%20-%20g%29%28%20-%202%29%20%3D%20%20%28%7B%20-%202%7D%29%5E%7B2%7D%20%20-%203%28%20-%202%29%20%2B%208%20%5C%5C%20%20%3D%204%20%2B%206%20%2B%208%20%5C%5C%20%20%3D%2010%20%2B%208)
</h3>
We have the final answer as
<h3>
![(h - g)( - 2) = 18](https://tex.z-dn.net/?f=%28h%20-%20g%29%28%20-%202%29%20%3D%2018)
</h3>
Hope this helps you
Answer:
4x
Step-by-step explanation:
When multiplying a number by a variable the number is written first and then the variable. It can be represented like this: 4(x). If you simplify that you get 4x.
For the second question (5/6)/(4) is the same as (5/6)*(1/4) so just multiply across and you get (5/24)